Validity and Reliability of Hospitalization Anxiety Scale Based on Parent Perception in Children Age 1-6 Years : Validitas dan Reliabilitas Skala Kecemasan Rawat Inap Berdasarkan Persepsi Orang Tua Persepsi pada Anak Usia 1-6 Tahun - Hermalinda Herman; Apiradee Pimsen; Lili Faria; Deswita; Okky Adelirandy; Rahmatika Amelda; Rahmi Ramadhan (NERS Jurnal Keperawatan, 2023)
Hospital is a stressful experience for both children and their families. The main stressors could be in the form of separation from family, loss of control, bodily injury, and pain. In clinical practice, nursing assessments in identifying anxiety in children and parents were often challenging. Nurses tended to focus on the physical problem of children than on physiological respond. This research aimed to test the validity and reliability of parents' perception scale about hospitalization anxiety of children aged 1-6 years. The research used a descriptive-analytic research design with a cross-sectional study approach. The sample in this research were 34 parents taken by accidental sampling technique. The sample criteria were children undergoing hospitalization aged 1-6 years and being treated for more than one day. Data were collected using a questionnaire for parents' perceptions about the anxiety of hospitalization for children aged 1-6 years. This questionnaire consisted of 18 items ranging from never to often. The researcher used the Cronbach alpha test and Pearson product-moment to analyze the data. The results showed that 15 items were valid and reliable (r > 0.339) and Cronbach's Alpha value = 0.885). We could conclude that the scale was valid and reliable in measuring parents' perceptions about the anxiety of hospitalization for children aged 1-6 years. Further research was needed to test the effectiveness of this scale in a practical setting.